Crystal structure of benzylammonium 2, 3, 4, 5-tetrabromo-6- (methoxycarbonyl)benzoate, (C7H10N)+(C9H3Br4O4)–, C16H13Br4NO4 - Li Jian (Zeitschrift für Kristallographie - New Crystal Structures, 2012)
C16H13Br4No4, monoclinic, P21/c (no. 14), a = 18.883(2) Å, b = 16.095(2) Å, c = 14.023(1) Å, β = 109.785(1)°, V = 4010.5 Å3, Z = 8,Rgt(F) = 0.0533, wRref(F2) = 0.1064, T = 298 K.